Molecular engineering of simple carbazole-arylamine hole-transport materials for perovskite solar cells. Issue 4 (3rd February 2020) - Liu, Xuepeng; Ma, Shuang; Mateen, Muhammad; Shi, Pengju; Liu, Cheng; Ding, Yong; Cai, Molang; Guli, Mina; Nazeeruddin, Mohammad Khaja; Dai, Songyuan
Abstract : N, N -Dimethylamino-based carbazole-arylamine hole-transport materials show better performance than methylsulfanyl or methoxy counterparts in perovskite solar cells, and even exhibit higher efficiency and extremely lower laboratory synthesis cost than conventional spiro-OMeTAD. Abstract : We report synthesis and characterization of novel hole-transport materials (HTMs) with substituents, methylsulfonyl, N, N -dimethylamino or methoxy groups, introduced onto the N of the carbazole unit of carbazole-arylamine and their application in perovskite solar cells (PSCs). We found that the new HTMs with a N, N -dimethylamino substituent exhibit superior hole extraction ability despite lower carrier mobility than that of methylsulfonyl and methoxy counterparts. After careful optimization of HTM concentration and deposition conditions, the PSCs using pristine and doped N, N -dimethylamino-based HTMs show a promising efficiency of 16.12% and 19.25%, respectively. Our findings unravel the influence of functional groups on power conversion efficiency of perovskite solar cells.